2004
DOI: 10.1007/s00018-004-4288-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human epidermal stem cells by adherence and the reconstruction of skin equivalents

Abstract: The isolation of human epidermal stem cells is critical for their clinical applications. In the present study, we isolated three populations of epidermal keratinocytes according to their ability to adhere to collagen type IV: i.e., rapidly adhering (RA), slowly adhering (SA), and non-adhering (NA) cells. The aim of this study was to characterize RA cells and to investigate the possibility of using these cells for epidermis reconstruction. To identify RA cells, flow cytometric analysis was performed using anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
95
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 27 publications
2
95
1
2
Order By: Relevance
“…Recently, it was reported that p63 was involved in maintenance of epidermal stem cells and stratification of the epidermis (21). The fact that cells rapidly adhering to collagen type IV successfully perform epidermal reconstruction (22) proved that epidermal stem cells were located in the basal layer. The p63-expression in a wide area covering the basal to spinous layers observed in the present study may explain the two functional roles of this protein-sustaining stem cells in the basal layer and stratification of the epidermis in the spinous layer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that p63 was involved in maintenance of epidermal stem cells and stratification of the epidermis (21). The fact that cells rapidly adhering to collagen type IV successfully perform epidermal reconstruction (22) proved that epidermal stem cells were located in the basal layer. The p63-expression in a wide area covering the basal to spinous layers observed in the present study may explain the two functional roles of this protein-sustaining stem cells in the basal layer and stratification of the epidermis in the spinous layer.…”
Section: Discussionmentioning
confidence: 99%
“…2I-L). It has been noted that stem cells isolated from other tissues such as the skin and hair follicle [43][44][45] have smaller cell sizes than their more differentiated progeny. The SP cell frequency in rat corneal epithelium (4.6%) was also much higher than in the limbus, as well as results reported for several tissues and organs [13,16,20,23], and the presence of corneal epithelial SP cells in rat eyes were contrary to our previous results for both human [23] and rabbit [24].…”
Section: Discussionmentioning
confidence: 99%
“…cell-like properties we have chosen here a functional method based on the cellular adherence to collagen IV. This method has been reported to successfully enrich for cells with stem cell-like properties in various epithelial tissues, such as normal human skin 13,30 . This method has been shown to robustly sort cell populations with different self-renewing capacities 13 and different potential for regenerating normal skin 30 and OSCC 5a .…”
Section: Discussionmentioning
confidence: 99%
“…This method has been reported to successfully enrich for cells with stem cell-like properties in various epithelial tissues, such as normal human skin 13,30 . This method has been shown to robustly sort cell populations with different self-renewing capacities 13 and different potential for regenerating normal skin 30 and OSCC 5a . We have chosen to use this method for CSC enrichment since it avoids possible cell surface modifications that might occur due to antibody binding, and thus prevents any alterations of their original electrophysiological properties that would occur after marker-based cell sorting.…”
Section: Discussionmentioning
confidence: 99%